Utricularia kumtensis (Lentibulariaceae): a new species from Konkan region of Uttara Kannada District, Karnataka - Kanoj, Manjushree Suresh; Patgar, Vanaja Ganapati; Betageri, Shreyas; Katrahalli, Kotresha (Phytotaxa, 2025)
Utricularia kumtensis, a new species of lithophytic bladderwort has been described with photographs, illustration and seed morphometry from Coastal belt of Uttara Kannada district, Karnataka. Utricularia kumtensis differs from U. striatula in its flower size, half-open flower, three lobed lower petal, small spur and seed morphometry.